Argentina y el reto de los objetivos de desarrollo del milenio. Una mirada a través de la lucha contra la pobreza como objetivo país - Surasky, Javier (Revista Española de Desarrollo y Cooperación, 2023)
In this paper we review the relationship between Argentina and the Millennium Development Goals (MDGs), marked by the hard political times that the country experienced in the years immediately following the Millennium Summit of the United Nations.